Improvement in condition-specific and generic quality of life outcomes in patients with knee osteoarthritis following single-injection Synvisc: results from the LOBRAS study. (4th March 2017) - Kearey, P.; Popple, A.E.; Warren, J.; Davis, T.; Bellamy, N.; ,
Abstract: Objective: To evaluate the effectiveness of viscosupplementation with single-injection hylan G-F20 (Synvisc-One) in knee osteoarthritis (OA), during routine clinical care, in a 52 week observational study. Research design and methods: The LOBRAS study involved a 1 year long, multi-center, quasi-experimental, repeated measures, observational study. Consenting patients in Australia fulfilling inclusion/exclusion criteria under the care of a medical specialist in routine clinical practice were enrolled. Prior to, and for 52 weeks following, intra-articular single-injection hylan G-F20, patients were repeatedly evaluated using the WOMAC NRS4.1 Index and the SF-36 questionnaire. The WOMAC NRS4.1 was administered by mobile phone (with paper back-up), and the SF-36 was administered on paper. Patients were monitored for adverse events. Main outcome measures: Western Ontario and McMaster (WOMAC) OA Index, and the Short Form 36 questionnaire (SF-36 v2). Results: A total of 131 patients with knee OA were enrolled, of whom 119 provided both pre- and post-intervention WOMAC data. Statistically significant improvements (with a maximum of p ≤ .025) from baseline to Week 12, Month 6 and Week 52 were detected, by intention-to-treat (ITT) and per-protocol (PP) analyses, in WOMAC Pain, Stiffness, Function, PGA, and Total Score, SF-36 PCS, and WOMAC-derived HUI3. Adverse event (AE) monitoring detected treatment-related AEs in 5.3% of patients. Conclusions: The effectiveness of single-injection hylan G-F20 in routine clinical care is supported by the detection of statistically significant, clinically important improvements in WOMAC Pain, Stiffness, Function, Total, and PGA outcomes, and statistically significant improvements in SF-36 PCS and WOMAC-derived HUI3 outcomes at multiple time points. Limitations of this study include lack of a control group or blinding. No predictive indicators of the response to treatment were identified. In general single-injection hylan G-F20 was well tolerated with very few patients experiencing any treatment-related adverse events. Collectively, these observations attest to the effectiveness of single-injection hylan G-F20 and complement previous observations in routine clinical care.